Ukraine’s debt security in the context of military conflict (Law and Safety, 2023)
In the context of military conflict, security issues come to the fore in all spheres of state life. As the combat capability of the army largely depends on the financing of its needs, the problem of finding additional financial resources is becoming more acute. However, the economy is currently unable to cope with this task due to the destruction of the material and technical base and logistics routes, military mobilisation of some employees, the outflow of labour resources abroad and other factors resulting from the armed aggression. Therefore, the search for ways to improve debt security in the context of a military conflict is of utmost importance.The purpose of the article is to identify the ways to increase the level of debt security of Ukraine's economy. To achieve this goal, the state, dynamics and structure of public and publicly guaranteed debt for 2013–2022 have been analysed. It has been established that over the past ten years, the volume of total public debt has been steadily increasing. This was mainly due to an increase in such components as direct public and external debt. The fastest growth in total public and publicly guaranteed debt was in the years of military operations.The analysis of the state debt security indicators has shown a deterioration in the state of debt security and the approach of a debt crisis. Due to the significant complication of the conditions in which Ukraine's economy has been operating over the past year, it is proposed to revise the Medium-Term Public Debt Management Strategy for 2021–2024 to define new targets and approaches in this area. Currently, the Ministry of Finance's main task is to restructure domestic and external debt.In order to increase the level of debt security of Ukraine, it has been proposed to initiate the development of an international protocol for debt cancellation for countries affected by armed aggression. In the course of domestic debt restructuring, it has been suggested that the yield on domestic government bonds should be reduced, but this can only be done if monetary policy is changed.
Keywords: state debt security; indicators of state debt security; state and state-guaranteed debt; external state debt; internal state debt; state debt restructuring; debt obligations; state debt management.